The Importance of Digitalization in Shaping the Future of Higher Education: Between Challenge and Innovation - Alajeel, Haytam Basheer (Sharwes Scientific Journal, 2025)
Higher education platforms are undergoing a qualitative transformation driven by the digital revolution, wherein digital technologies transcend their role as mere auxiliary tools to become primary catalysts for enhancing educational quality. This study explores the mechanisms through which digitalization contributes to elevating innovation and creativity, transforming the learning environment into a dynamic space that encourages discovery and self-knowledge. This is demonstrated through a practical case study of our experience with students from the Faculty of Law and Sharia at Nalut University (Libya), aimed at improving the quality of educational outcomes. By analyzing this experience and observing the reality and prospects of digitalization in higher education in Algeria, we have reached conclusions that yielded recommendations designed to position digitalization as a locomotive driving higher education in both countries towards new horizons. This will be achieved through investment in infrastructure, content development, and empowerment of personnel, thereby contributing to a radical transformation in educational quality and preparing a generation capable of confronting contemporary challenges, ultimately building a modern educational system reliant on technology, capable of equipping students with the necessary skills to build the future.